Técnicas de geotecnologia na avaliação na área erodida na Bacia Hidrográfica Dois Córregos, Selviria-MS - Machado, Oscar Domingos Bergamaschi [UNESP] (2013)
A study was conducted in an environmental multitemporal erosion in the whatershed of the river Dois Córregos using satellite images of the year 2011, aerial photographs of 1965 and topographics techniques. To conduct this research we used the geotools called geographic information systems, global positioning systems and remote sensing. A eroded in the whatershed of the river Dois Córregos was chosen owing to the large volume of soil deposited along the river and even there servoir Hydropower Plant Jupiá and can be observed easily through satellite images or even in field expeditions. The whatershed of Dois Córregos is located over the Guarani Aquifer, which has an area of 52,985.39 hectare and plays an important role in providing fresh water to the reservoir surface of Hydropower Plant Jupiá. The objective of this study was the techniques analysis linked to the geotechnologics of a eroded area in the whatershed of the river Dois Córregos using low-costs tools and getting results that can help recover this area